4y+(9x+2y)=
3z+8+(7-2z)=
9x-(3x+2)=
10x+7-(9-2x)=
6a+7-9b-(-9-3a)=
3bc+7a-(-4bc+8a)=
(4a-2)+(6b-9)=
-(9a+7)+(3a-6)=
-(6a+7)-(-7+16a)=
4ab-2b-(-9ab+8b)=
-(-3a-9)-(6a-5)=
(2a-7)-(5-4a)=



Odpowiedź :

Odpowiedź:

4y+(9x+2y)=6y+9x

3z+8+(7-2z)=z+15

9x-(3x+2)=12x-2

10x+7-(9-2x)=12x-2

6a+7-9b-(-9-3a)=6a+7-9b+9+3a=3a-9b+16

3bc+7a-(-4bc+8a)=3bc+7a+4bc-8a=7bc-a

(4a-2)+(6b-9)=4a-11+6b

-(9a+7)+(3a-6)= -9a-7+3a-6= -6a-13

-(6a+7)-(-7+16a)= -6a-7+7-16a= -22a

4ab-2b-(-9ab+8b)=4ab-2b+9ab-8b=13ab-10b

-(-3a-9)-(6a-5)=3a+9-6a+5= -3a+14

(2a-7)-(5-4a)=2a-7-5+4a=6a-12

Szczegółowe wyjaśnienie:

Odpowiedź:

4y + (9x+2y)= 4y +9x +2y= 6y +9x

3z +8 + ( 7-2z)= 3z +8 +7 -2z= z +15

9x  - ( 3x+2)= 9x -3x  -2= 6x-2

10x+7 - ( 9-2x)= 10x + 7 -9 +2x= 12x  -2

6a+7 -9b - ( -9-3a)= 6a+ 7 -9b +9 +3a= 9a -9b +16

3bc +7a  - ( -4bc +8a)= 3bc +7a  +4bc -8a = 7bc -a

( 4a-2) + ( 6b-9)= 4a-2 +6b -9= 4a +6b  -11

-( 9a +7) +( 3a-6) = -9a -7  +3a  -6= -6a -13

 - (6a+7) - (- 7 +16a)= -6a  -7 +7 -16a= -22a

4ab-2b - (- 9ab+8b)=   4ab -2b +9ab -8b= 13ab -10b

- (- 3a-9) - ( 6a-5)= 3a +9 -6a +5= -3a  +14

  ( 2a-7 ) - ( 5-4a)= 2a-7 -5 +4a= 6a -12

Szczegółowe wyjaśnienie:

Inne Pytanie